Effects of nutrient management on productivity of T. aman-mustard (relay crop) - Boro rice pattern - Haque, M A; Ashrafi, R; Nahar, K (Bangladesh Journal of Nuclear Agriculture, 2025)
An experiment was conducted to find out the effect of different doses of chemical fertilizers with the integrated use of vermicompost in 3 crops cropping pattern [T. aman-Mustard (relay crop) - Boro] and to find out optimum fertilizer doses of mustard under relay crop as well as the whole cropping system at the BINA Substation farm, Ishwardi during 2023 to 2024. Mustard was grown as relay crop with T. aman. Six treatments were used in the experiment which were T1: 100% PKS from chemical fertilizer (CF), T2: 100% NPKS from CF, T3: 100% P from VC + 100% NKS from CF (IPNS), T4: 100% P from VC + 100% NKS from CF (non-IPNS), T5: 50% K from VC + 50% K from CF +100% NPS from CF (IPNS) and T6: 50% K from VC + 50% K from CF + 100% NPS from CF (Non-IPNS) for T. aman rice (Binadhan-17) and T1: Native soil fertility, T2: 100% NPKS, T3: 75% NPKS, T4: 125% NPKS, T5: 150% N + 100% PKS and T6: 75% NPKS + 2 t/ha VC for Mustard (Binasharisha-11) and Boro rice (Binadhan-14). The experiment was laid out in a randomized complete block design with three replications. In the first crop of the cropping pattern, the treatment T3 (6.5 t ha-1) produced maximum grain yield of T. aman rice followed by the treatment T5 (6.2 tha-1) which indicated that 100% P from VC+ 100% NKS from CF (IPNS) reduced the application of 100% P fertilizer from CF. In the second crop (Mustard) the treatment T4 (125% NPKS) produced maximum seed yield of mustard (1.02 t ha-1) which was statistically similar to all other treatment except the treatment T1 (0.21 t ha-1). In the third crop (Boro rice), the treatment T4 (125% NPKS) produced maximum grain yield of Boro rice (6.2 t ha-1) followed by the treatment T5 (6.00 t ha-1). As per total field duration for the cropping pattern was 308 which were 14 days more than the cropping pattern considering mustard as relay crop. This demonstrates that relay cropping of mustard with T. aman reduces total length of T. aman- mustard (relay crop) - Boro cropping pattern and also offers earlier sowing of mustard. Results also indicated that fertilizer doses (kgha-1) N75P0K26S7VC352, N107P24K54S22Zn2B2 and N161P18K67S13 were found better considering yield performance and economic potentiality of T. aman, mustard and Boro, respectively. For the whole cropping pattern BCR was found 2.06 which demonstrate the cropping pattern is cost effective and potentially acceptable. Bangladesh J. Nuclear Agric., 39(1): 77-86, 2025